Validity comparison of CAT (caries risk assessment tool) and CAMBRA (caries management by risk assessment) on children: a rapid review - Raisya Aurellia Putri LESMANA; Anne Agustina SUWARGIANI; Meirina GARTIKA (Dentistry Faculty, 2022)
Caries Risk Assessment (CRA) focuses on caries prevention than restorative approaches. CariesManagement by Risk Assessment (CAMBRA) and Caries Risk Assessment Tool (CAT) are examples of manualcharting CRA methods that were made to make it easier for clinicians and non-clinicians. This study aims tocompare the validity of CAMBRA and CAT as CRA for children. This study is a rapid review and uses articles asresearch samples. Systematic searching was carried out using the PRISMA diagram. This study uses PubMed andScience Direct databases. This study includes randomized controlled, cohort, and methodological studies reportingthe validity of CAT and CAMBRA methods on children published from 2011-2021. Searching strategy for this studyis (children) AND (dental caries) AND (risk assessment) AND ((CAT) OR (CAMBRA) OR (AAPD)) AND (validity).Articles that meet the inclusion criteria will be extracted and discussed. One hundred three articles were identified,and only five articles met the inclusion criteria. Modified CAT by adding the patient's Streptococcus mutansexamination without asking the patient's social-economic status has the highest validity value. The method with thelowest validity value in this study is the unmodified CAT method. Both CAMBRA and CAT validity are stilllimited. The evidence is still low. CAT has high sensitivity score but a low specificity value, while the CAMBRAmethod has a different validity value for each reported article.KEYWORDS: Caries risk assessment, children, Caries Management by Risk Assessment (CAMBRA), Caries RiskAssessment Tool (CAT), validity